2007
DOI: 10.1080/10826080701212360
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Reported Current and Lifetime Substance Abuse Problems Among a National Sample of U.S. Homeless

Abstract: Using the National Survey of Homeless Assistance Providers and Clients (NSHAPC), this study examined predictors of alcohol and drug problems among a national probability sample of homeless and previously homeless adults in the United States. Consistent with research, about one third and one quarter of the respondents reported a current alcohol and drug problem, respectively. A larger proportion reported lifetime substance abuse problems. As hypothesized, males, younger respondents, veterans, and those with men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 27 publications
0
12
1
Order By: Relevance
“…The current study provides a comprehensive perspective of homelessness in an older adult population by including recruiting venues through which homeless people transition. Because Oakland has a higher proportion of African-Americans than the country as a whole, our sample has a larger proportion of African-Americans (Dietz, 2007; Hahn et al, 2006; Kushel et al, 2002), although the relative proportions (3–4 times the general population of the region) are similar. Similar to other studies of older homeless adults, we found a higher rate of chronic illness (Hahn et al, 2006), cognitive impairments (Buhrich et al, 2000; Fischer et al, 1986), and a lower rate of active illicit drug use than younger samples (Gelberg et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…The current study provides a comprehensive perspective of homelessness in an older adult population by including recruiting venues through which homeless people transition. Because Oakland has a higher proportion of African-Americans than the country as a whole, our sample has a larger proportion of African-Americans (Dietz, 2007; Hahn et al, 2006; Kushel et al, 2002), although the relative proportions (3–4 times the general population of the region) are similar. Similar to other studies of older homeless adults, we found a higher rate of chronic illness (Hahn et al, 2006), cognitive impairments (Buhrich et al, 2000; Fischer et al, 1986), and a lower rate of active illicit drug use than younger samples (Gelberg et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Most health problems are distributed unevenly within the homeless population (see, e.g., Dietz 2007, Lee & Greif 2008). Problems that vary by race, gender, or age in housed samples usually do so among the homeless.…”
Section: Life Chancesmentioning
confidence: 99%
“…These disorders are common among homeless persons, with prevalence estimates of 40% to 60%. 25,26 These individuals generally have significantly greater health care needs, for treatment of, for example, psychiatric disorders, HIV and other sexually transmitted infections, hepatitis, liver disease, lung disease, and wound and skin infections. 2730 The premature mortality rate is significantly higher for homeless individuals than for the general population, 27,31 and homeless people with substance use disorders are even more disproportionately affected.…”
mentioning
confidence: 99%